Chad : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2013)
This paper analyzes the effect of an IMF Staff-Monitored Program for Chad to enhance economic development. Weak institutional capacity and governance concerns have limited economic development and donor support in Chad. It is highlighted that the reduction in the nonoil primary deficit envisaged in the 2013 budget appears appropriate, but expenditures linked to the regional security situation and lower than anticipated oil revenues imply large financing needs. There are significant economic and political risks to program implementation,; the regional security situation remains volatile, and the economy is highly dependent on volatile oil revenue.